The potential role of betaine in enhancement of microbial-assisted phytoremediation of benzophenone-3 contaminated soil. (November 2022) - Wang, Wenjing; Liu, Anran; Chen, Xiancao; Zheng, Xiaoyan; Fu, Wenting; Wang, Gang; Ji, Jing; Jin, Chao; Guan, Chunfeng
Abstract: Benzophenone-3 (BP-3) is an emerging environmental pollutant used in personal care products, helping to reduce the risk of ultraviolet radiation to human skin. The BP-3 removal potential from soil by tobacco ( Nicotiana tabacum ) assisted with Methylophilus sp. FP-6 was explored in our previous study. However, the reduced BP-3 remediation efficiency by FP-6 in soil and the inhibited plant growth by BP-3 limited the application of this phytoremediation strategy. The aim of the present study was to reveal the potential roles of betaine, as the methyl donor of methylotrophic bacteria and plant regulator, in improving the strain FP-6-assisted phytoremediation capacity of BP-3 contaminated soil. The results revealed that strain FP-6 could use betaine as a co-metabolism substrate to enhance the BP-3 degradation activity. About 97.32% BP-3 in soil was effectively removed in the phytoremediation system using tobacco in combination with FP-6 and betaine for 40 d while the concentration of BP-3 in tobacco significantly reduced. Moreover, the biomass and photosynthetic efficiency of plants were remarkably improved through the combined treatment of betaine and strain FP-6. Simultaneously, inoculation of FP-6 in the presence of betaine stimulated the change of local microbial community structure, which might correlate with the production of a series of hydrolases and reductases involved in soil carbon, nitrogen and phosphorus cycling processes. Meantime, some of the dominant bacteria could secrete various multiple enzymes involved in degrading organic pollutants, such as laccase, to accelerate the demethylation and hydroxylation of BP-3. Overall, the results from this study proposed that the co-metabolic role of betaine could be utilized to strengthen microbial-assisted phytoremediation process by increasing the degradation ability of methylotrophic bacteria and enhancing plant tolerance to BP-3. The present results provide novel insights and perspectives for broadening the engineering application scope of microbial-assisted phytoremediation of organic pollutants without sacrificing economic crop safety. Graphical abstract: Image 1 Highlights: FP-6 used betaine as a co-metabolism substrate to enhance BP-3 degradation activity. Betaine markedly improved the growth performance of tobacco exposed to BP-3 stress. Combined application of betaine and strain FP-6 enhanced plant tolerance to BP-3 stress. Betaine enhanced strain FP-6-assisted phytoremediation of BP-3 contaminated soil. Strain FP-6 and betaine changed the soil enzyme activities and microbial community.